Conceptualising airport digital maturity and dimensions of technological and organisational transformation - Halpern, Nigel; Budd, Thomas; Suau-Sanchez, Pere; Bråthen, Svein; Mwesiumo, Deodat (Henry Stewart Publications, 2021)
As airports undergo digital transformation, ie a paradigmatic shift in the way digital technologies are adopted and used, there is a need for actionable insights to ensure that airport digital maturity is achieved. Using an integrative review of literature, this paper develops an airport digital maturity model, focusing mainly on a passenger experience perspective. The paper then delineates two dimensions of digital transformation — technological and organisational. Subsequently, an airport digital transformation model is conceptualised to identify key factors that airports need to consider when transforming their business and interesting lines of enquiry for future research. Insights offered by the model are relevant to both practitioners and researchers interested in conducting future studies in this area.
Keywords: digital transformation; maturity models; airports